Adapting to uncertainty: Agricultural practices and policies in the Al-Ghab Plain, Syria - Auda, Ammar; Szilvácsku , Miklós Zsolt (4D Journal of Landscape Architecture and Garden Art, 2025)
Ghab Plain is a historically important agricultural region in Syria. Since 2011, the Syrian crisis has impacted its agricultural productivity, and worsened socio-economic conditions. This study investigates the current state of agricultural production in Ghab and examines how rural livelihoods have adapted to the socio-economic and environmental disruptions caused by the Syrian crisis. Using a case study approach, data were collected through semi-structured interviews with seven key informants from agricultural cooperatives in the region. The research highlights the decline of the agricultural sector primarily due to damaged irrigation infrastructure, escalating production costs, and insufficient government support. In response, many farmers have shifted to small-scale farming focused on household self-sufficiency, diversifying crop production, and raising domestic livestock. The study suggests that enhancing agricultural resilience in Ghab requires promoting organic fertilizers, increasing local feed production, and implementing contract farming. The rehabilitation of irrigation infrastructure is also critical. These findings underscore the resilience of rural communities in the face of adversity and offer insights into policy measures that could support the recovery of Syria’s agricultural sector. Further comparative studies across different Syrian regions are needed to fully understand the varying impacts of the conflict on agriculture.
Keywords: Agricultural resilience; Al-Ghab Plain; Contract farming; Rural livelihoods; Syria